Application of Hazard Analysis and Critical Control Points (HACCP) on The Production Process Line of Noni Juice Drink (Morinda Citrifolia L.) - Richardus Widodo; Wahyu Kanti Dwi Cahyani; Tulus Yudi Widodo Wibowo; Anita Wulandari (Universitas Dr Soetomo, 2022)
Hazard analysis and critical control point (HACCP) is a preventive system to ensure food safety. This enables product protection and error correction, reduces costs due to quality defects and reduces overcontrol of the final product. Collecting data using in-depth interviews, field observations, and study of documents owned by the research object. The HACCP system is applied to the noni juice production line in UD Manjur Makmur Lumajang. this small industry is seeking marketing approval from the BPOM (Food and Drug Supervisory Agency). Therefore, in order to follow the HACCP concept and ensure the safety of the food produced, some changes are required in the production process. Determination of critical control points (CCP) has focused on activities that are considered critical to pose a hazard, critical limits at each critical control point have also been determined The main hazards found were in sorting, seal opening and pouring in a press. The application of the HACCP principle will enable more accurate control of the noni juice production process.